The anthropocene and apocalypticism in Jeet Thayil’s Low - Daniel, Subin T; Mishra, Binod (Penerbit Universiti Kebangsaan Malaysia, 2024)
Jeet Thayil’s Low is based on the central theme of grief and agony, which the protagonist, Dom, faces after the sudden loss of his wife, Aki. In search of a haven, he runs to Mumbai, which mirrors the broken protagonist. Along with Dom’s struggle to find a clean water source to immerse Aki’s ashes, Thayil presents various major environmental concerns like pollution, global warming, the rising sea level, waste management, etc., which can be traced back to the Anthropocene. He also warns against an impending apocalypse. This study addresses the ecocritical elements in Thayil's Low, the representation of urban space plagued by ecological hazards, and a possible global annihilation in the future. Thayil, with a touch of personal grief, moves into the terrains of ecological grief and eco-anxiety as he portrays today’s urbanscapes and warns about the times to come, which transverses into the realm of climate fiction.